2012
DOI: 10.1371/journal.pone.0046355
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Stereocilia of Hair Cells by Forced Atoh1 Expression in the Adult Mammalian Cochlea

Abstract: The hallmark of mechanosensory hair cells is the stereocilia, where mechanical stimuli are converted into electrical signals. These delicate stereocilia are susceptible to acoustic trauma and ototoxic drugs. While hair cells in lower vertebrates and the mammalian vestibular system can spontaneously regenerate lost stereocilia, mammalian cochlear hair cells no longer retain this capability. We explored the possibility of regenerating stereocilia in the noise-deafened guinea pig cochlea by cochlear inoculation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 49 publications
(69 reference statements)
0
73
0
Order By: Relevance
“…The mouse was anesthetized with a mixture of ketamine/xylazine (ketamine 100 mg/kg; xylazine 15 mg/kg; ip), and supplemented as needed. ABRs were recorded in response to tone bursts of 2, 4, 8, 16, 22, and 32 kHz using standard procedures previously described [25,26]. Tone pipe with 1 ms rise cosine on/off ramps were generated digitally using a clock rate of 125 kHz and 16-bit D/A converters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mouse was anesthetized with a mixture of ketamine/xylazine (ketamine 100 mg/kg; xylazine 15 mg/kg; ip), and supplemented as needed. ABRs were recorded in response to tone bursts of 2, 4, 8, 16, 22, and 32 kHz using standard procedures previously described [25,26]. Tone pipe with 1 ms rise cosine on/off ramps were generated digitally using a clock rate of 125 kHz and 16-bit D/A converters.…”
Section: Methodsmentioning
confidence: 99%
“…The bulla was perforated allowing for exposure of the stapedial artery, basal turn, and apical turn of the cochlea. A silver electrode was placed on the ridge near the round window for recording CM [25]. The ground electrode was implanted in the dorsal neck muscles.…”
Section: Methodsmentioning
confidence: 99%
“…Several mutations that interfere with stereocilia bundle organization and homeostasis are known (Hertzano et al, 2008;Kitajiri et al, 2010;Mogensen et al, 2007;Sekerková et al, 2011) and many of these result not only in aberrant bundle morphology but also in the death of HCs (Kersigo and Fritzsch, 2015;Self et al, 1998;Ueyama et al, 2014). Consistent with a role of Atoh1 in stereocilia differentiation, forced expression of Atoh1 can restore hair bundles (Yang et al, 2012).…”
Section: Neurog1 Misexpression With Transient Expression Of Atoh1 Resmentioning
confidence: 99%
“…Previous studies of Atoh1 mutant mice have revealed multiple functions of Atoh1 in the genesis, survival, maturation, and function of hair cells (Bermingham et al, 1999;Chen et al, 2002;Woods et al, 2004;Pan et al, 2012;Yang et al, 2012b;Cai et al, 2013). Overexpression of Atoh1 in immature rodent inner ears can induce ectopic hair cells in both sensory and nonsensory regions of the cochlea (Zheng and Gao, 2000;Woods et al, 2004), suggesting the sufficiency of Atoh1 for hair-cell formation in parts of the inner ear.…”
Section: Introductionmentioning
confidence: 99%